Trinity Week Academic Symposium - Origins, mission and significance - Daly, Mary E. (Statistical and Social Inquiry Society of Ireland, 2007)
This symposium celebrates the launch of a dedicated website of the proceedings of the Statistical and Social Inquiry Society of Ireland, and its direct ancestor the Dublin Statistical Society. The Dublin Statistical Society was founded on 23 November 1847 with the mission to bring professional expertise to bear on pressing contemporary social and economic issues. The timing is not coincidental: 1847 was probably the worst year in the history of modern Ireland. This was the beginning of the third year of the great famine; death and emigration were at record levels, as was the incidence of disease. The British government was suffering from `compassion fatigue?; they had ended all special measures for famine relief and abandoned Ireland to its own resources, placing the entire burden of relief on the inadequate and inexperienced Irish Poor Law, which was breaking down under the strain. Landlords, faced with record rates bills and unpaid rents were evicting tenants and clearing their estates, and the emigrant ships contained not just the destitute and desperate, but many substantial farmers with their families. An international financial crisis only added to the gloom. Irish politics was also in disarray, following the death of Daniel O?Connell and the collapse of the Irish Convention which had attempted to achieve some political consensus on critical issues such as land reform.
Origins, mission and significance [of the Statistical and Social Inquiry Society of Ireland]
Read before the Society, 16 May 2007
Keywords: Statistical and Social Inquiry Society of Ireland; Social history; Economic history; Statistics; 314.15